Development of geopolymers from plasma vitrified air pollution control residues from energy from waste plants - Kourti, Ioanna; Amutha Rani, D.; Deegan, D.; Cheeseman, C. R.; Boccaccini, Aldo R. (Ceramic Transactions, 2010)
The aim of this study was to develop low energy sustainable geopolymers using DC plasma vitrified Air Pollution Control (APC) residues as the main component. APC residues are generated from the air pollution abatement systems of Energy from Waste (EfW) plants. They are classified as hazardous waste because of their high alkalinity, heavy metal and soluble salt content. DC plasma technology combines APC residues with glass forming additives at temperatures above 1400°C and produces a stable, non-hazardous inert glass that has been qualified as a product for potential beneficial reuse. In this research plasma vitrified glass has been used to develop geopolymers. The effect of NaOH concentration and curing time on compressive strength is reported. The microstructure of selected APC geopolymer samples was investigated by SEM, X-ray diffraction and SEM/EDS analysis. In order to evaluate the potential for using this material in a range of construction applications the density and water absorption were assessed. Optimum APC glass geopolymers were prepared with 6M NaOH in the activating solution resulting in compressive strengths of ∼110 MPa after 28 days. This material had high density (2070 kg/m3), low water absorption (11%) and low porosity. The results demonstrate that the glass derived from DC plasma vitrification of APC residues can be used to form high strength geopolymers, with potential for use in a range of applications.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.develo